Discovery of Efficient Visible‐light Driven Oxygen Evolution Photocatalysts: Automated High‐Throughput Computational Screening of MA2Z4. (28th August 2022) - Lin, Chao; Feng, Xiang; Legut, Dominik; Liu, Xiaopeng; Seh, Zhi Wei; Zhang, Ruifeng; Zhang, Qianfan
Abstract: Photocatalytic oxygen evolution reaction (OER) by 2D semiconductors is a promising strategy for efficient energy conversion. The newly discovered 2D semiconductors MA2 Z4 (M = transition metal, e.g., Mo, W; A = C, Si, and Ge; Z = N, P, and As) have shown characteristics of promising photocatalytic OER catalysts. Herein, an automated high‐throughput workflow is proposed to efficiently screen MA2 Z4 photocatalytic OER catalysts, and further reveal the theoretical mechanism. The four criteria of semi‐conductivity, bandgap width/band edge position, structural stability, and free energy change, are proposed to screen MA2 Z4 catalysts thermodynamically. The exciton properties and carrier mobility of these MA2 Z4 are further studied to explore the high‐efficiency photocatalytic OER MA2 Z4 with low exciton binding energy and high effective mass ratio. It is found that the bandgap width of MA2 Z4 mainly depends on the strength of MZ bonding and the redistribution of electrons, while the catalytic effect is closely related to the adsorption capacity of O atom. In particular, β‐ZrSi2 N4 and β‐HfSi2 N4 are screened as efficient photocatalytic OER catalysts. This study develops a fully automated method and contributes to a complete framework for screening high‐efficiency photocatalytic OER catalysts. Abstract : An automated high‐throughput method to screen out promising MA2 Z4 candidates for photocatalytic oxygen evolution reaction. PBE bandgap, HSE bandgap/band edge position, phonon dispersions, free energy, GW+BSE absorption spectrum/exciton distribution, effective mass, and carrier mobility are used as judgment criteria to find efficient photocatalysts. Only β‐HfSi2 N4 and β‐ZrSi2 N4 meet all filters, they will be excellent catalysts for photocatalytic OER.